HYPONYMY IN PSYCHOLOGICAL TERMINOLOGY (TAMADDUN NURI JURNALI, 2025)
This article is dedicated to the study of the phenomenon of hyponymy, which is one of the important issues in the semantic field of modern linguistics. The article presents theoretical views on the introduction of the concept of hyponymy into linguistics and its characteristics. Examples of the occurrence of hypernym and hyponym phenomena in the terminology of psychology, which is one of the significant fields of linguistics, are provided and demonstrated.